THE INFLUENCE OF COMPETENCE, KNOWLEDGE, AND INCENTIVES ON THE PERFORMANCE OF POSYANDU CADRES IN THE BATU 10 PUBLIC HEALTH CENTER AREA THROUGH INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE - Kemistia Eva; Bambang Satriawan; Ana Faizah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Batu 10, one of the community health centers in Tanjungpinang City, currently has 135 cadres. Despite its large work scope, the number of Posyandu cadres is insufficient to meet the community's health service needs. Some cadres also serve as elderly health cadres, requiring them to handle more than one service desk. This results in an excessive workload and reduces the quality of service provided. This study used a quantitative method with a descriptive quantitative approach. The conclusion of this study is that competence, knowledge, and incentives significantly influence intrinsic motivation. Competence, incentives, intrinsic motivation, and competence also significantly influence performance, but knowledge does not. Intrinsic motivation cannot mediate the influence of competence, knowledge, or incentives on performance.